Autonomy and herbaceous forage in goat farming of western France. First results of a sociological survey - Inda D.; Jacquot A.-L.; Marnet P.-G.; Disenhaus C.; Flament J.; Coquard B.; Leroux B. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Our communication is based on the results of a multidisciplinary research (PSDR FLECHE – Fromages et Laits issus d’Élevages de Chèvres conduites avec de l’Herbe – 2016-2020) which aims to study the potential of grass utilization in goat systems, with the dual objective of strengthening the economic resilience of farms and the social image of the dairy goat sector of Western France. The latter currently represents almost half of the national goat population and 58% of the goat milk supplied in France. The sociological aspect of the research concerns the representations, value systems, interests and constraint systems (technical, economic, etc.) that guide the practices of all stakeholders in the sector: farmers, upstream and downstream actors. The objective of this approach is to analyse, at all levels of the value chain, the incentives and obstacles to a possible transition to grass-based feeding systems. Based on 76 semi-directive interviews, this paper presents the first results of this survey by showing how contextual elements (socio-economic, professional, etc.) impact farmers’ choices of practices. While, in principle, the whole goat sector seems to be converging towards an agro-ecological transition that ensures its sustainability, in practice, each stakeholder is confronted with a system of constraints that limits actual developments. The articulation of these obstacles seems to lead to a kind of inertia, which prevents the adoption of practices that are nevertheless perceived as recommendable by most stakeholders.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)